Computerized Attention Training Program and Vocal Ensemble Classes – means of Adolescent Attention Focusing Ability Development - Trubina, Irēna; Sīle, Maruta; Vaļēviča, Evita; Voita, Daina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Nowadays adolescents encounter difficulties focusing on particular, effective and long-term activities. These difficulties depend on their age group development regularities. The aim of the research is to evaluate computer attention training software in comparison with vocal ensemble classes on the subject of adolescent attention focusing ability development. Participants – 24 adolescents (both sexes, average age 14 ± 0,87 years) were divided into three experimental groups – experimental group A (EGA), experimental group B (EGB) and control group (KG). Two methods of adolescent attention focusing skills development were tested:computer software package CogniPlus /Schuhfried, Austria/ was applied to EGB and EGA used training system designed by music teachers and psychologists. It is concluded that supplementing vocal ensemble classes with attention focusing skills development training makes possible bigger improvement of attention focusing skills compared to computer training software.